Retinol Supplements Antiviral Action of Interferon in Patients with Chronic Hepatitis C: A Prospective Pilot Study - Kohge, Naruaki (the Society for Free Radical Research Japan, 2010)
Sustained virologic response with peg-interferon and ribavirin combination therapy for 48 weeks is still inadequate. Our study examined whether short-term administration of retinol clinically influences the anti-viral activity of interferon early during interferon and ribavirin combination therapy. The control group received 6 MIU of interferon α-2b every day for two weeks and then 3 times a week for 22 weeks intramuscularly plus 600 mg or 800 mg per day of ribavirin orally for 24 weeks. The retinol group, in addition to above treatment, received retinol 30,000 units per day orally for 3 weeks from one week before the start of interferon α-2b plus ribavirin combination therapy. The hepatitis C virus (HCV) RNA negativity rate at 1 week after the end of interferon α-2b and ribavirin combination therapy was 46.7% (28/60) for the retinol group and 31.7% (19/60) for the control group, which was significantly higher for the retinol group. The level of serum HCV RNA in the retinol group was significantly lower at 1 week after beginning treatment as compared to the control group (p<0.01). Furthermore, serum 2,5'AS protein at 1 week after beginning treatment was significantly higher in the retinol group (p = 0.0002). The results suggest that retinol supplement increases the antiviral effect of interferon α-2b plus ribavirin only during the administration of IFN α-2b, ribavirin and retinol in patients with chronic hepatitis C.